Online training to improve evidence-based leadership competencies among nurse leaders in Finland and China: study protocols for two randomised feasibility trials - Välimäki Maritta Anneli; Hipp Kirsi; Yang Min; Lantta Tella; Varpula Jaakko; Liu Gaoming; Tang Yao; Chen Wenjun; Hu Shuang; Chen Jiarui; Löyttyniemi Eliisa; Li Xianhong (BMJ PUBLISHING GROUP, 2025)
Introduction
This study protocol describes two randomised feasibility trials that will evaluate the feasibility and preliminary effectiveness of an online training course to improve evidence-based leadership competences among nurse leaders working in hospitals in Finland and China.
Methods and analysis
Two randomised, parallel-group studies will be conducted separately: one in Finland (n=140) and one in China (n=160). Nurse leaders who fulfil the eligibility criteria will be randomly allocated (1:1) to participate in either the online evidence-based leadership training or conventional online training (reading material only). The primary outcomes will be acceptance of the online course (logging into the platform) and adherence in the online course (returned course tasks and drop-out rate of the participants). The secondary outcomes will be acceptance of the study regarding recruitment, feasibility of the eligibility criteria and outcome measures and potential effectiveness of the online course on leadership skills, evidence-based knowledge, attitudes, practice, self-efficacy, self-esteem and intention to leave. In addition, the feedback will be asked after the course.
Ethics and dissemination
Two separate trials have received ethical clearance from local ethics committees (12/2022 in Finland, E2021167 in China). Permission to conduct the study will be granted by hospital authorities. All participants will provide electronic informed consent before baseline data are collected. The trial results will be published locally, nationally and internationally in professional and peer-reviewed journals, and shared at national and international meetings and conferences.
Trial registration numbers NCT05244512; NCT05244499.